Superfícies Mínimas em H3 e H2 x R - RUYS, Wesley da Silva (2008)
In this work we study some results from the article of Mercuri, F., Piu, P., Montaldo, S; Weierstrass Representation Formula for Minimal Surfaces in H3 and H2 x R. Therefore, we do a study of the minimal surfaces simply connected in three-dimensional Riemaniann manifold. Furthermore, searching for to determine the necessary conditions to find minimal surfaces in these spaces. Moreover, to give examples of the surfaces in the three-dimensional Heisenberg group and in the product of the hyperbolic with the real line.